2003
DOI: 10.1023/b:comp.0000018137.38458.68
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Dirichlet Series and Moments of Zeta and L-Functions

Abstract: Abstract. This paper develops an analytic theory of Dirichlet series in several complex variables which possess sufficiently many functional equations. In the first two sections it is shown how straightforward conjectures about the meromorphic continuation and polar divisors of certain such series imply, as a consequence, precise asymptotics (previously conjectured via random matrix theory) for moments of zeta functions and quadratic L-series. As an application of the theory, in a third section, we obtain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
193
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(195 citation statements)
references
References 29 publications
2
193
0
Order By: Relevance
“…If this can be done, the multiple Dirichlet series is said to be "perfect." This procedure has been carried out in detail for the Dynkin diagrams A 2 , A 3 and D 4 , see [14], [9], [6], [5], [4]. These multiple Dirichlet series give asymptotics for mean values of quadratic twists of L-functions on GL(1), GL(2) and GL(3).…”
Section: Dynkin Diagrams and Multiple Dirichlet Seriesmentioning
confidence: 99%
“…If this can be done, the multiple Dirichlet series is said to be "perfect." This procedure has been carried out in detail for the Dynkin diagrams A 2 , A 3 and D 4 , see [14], [9], [6], [5], [4]. These multiple Dirichlet series give asymptotics for mean values of quadratic twists of L-functions on GL(1), GL(2) and GL(3).…”
Section: Dynkin Diagrams and Multiple Dirichlet Seriesmentioning
confidence: 99%
“…Taking t = 0, the only terms that contribute will be those in the image of a map B λ −→ B λ+ρ , and the sum reduces to a sum over B λ . Thus when t = 0, the formula reduces to (32). Most importantly for us, taking t = q −1 and comparing with (29), we see that the sum over B λ+ρ is exactly δ 1/2 (a λ )W • (a λ ).…”
Section: Chinta-gunnellsmentioning
confidence: 82%
“…It is possible regard (4) as a multiple Dirichlet series, and indeed both (3) and (4) are treated together in Diaconu, Goldfeld and Hoffstein [32]. See [31] in this volume for a discussion of the sixth integral moment and its connection with the spectral theory of Eisenstein series on GL 3 .…”
Section: Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, our work is based on the convexity principle for holomorphic functions of two complex variables, whose use to study such series was first observed by Bump,Friedberg and Hoffstein [BFH2]. In [DGH, a similar point of view was taken. In particular, in [DGH] the approach of searching for a multiple Dirichlet series which is a weighted sum of twisted L-functions with a full meromorphic continuation in all variables was formalized.…”
Section: Introductionmentioning
confidence: 99%